Pengaturan Penipuan dalam Hukum Perdata: Studi Perbandingan KUHPerdata Indonesia dengan Nieuw Burgerlijk Wetboek Belanda - Ariyanto Ariyanto (Jurnal Penelitian Hukum De Jure, 2023)
A person who commits fraud will move something as if something happened and was right but the act does not correspond to reality. The purpose of this study is to examine the elements of Fraud in Article 1328 of the Indonesian Civil Code and examine the regulation of fraud (bedrog) in the civil code in the Netherlands. This research is a Normative Legal Research which is legal research carried out by examining library materials or secondary data. Normative legal research is also called doctrinal legal research. The results indicated that the explanation of the definition of fraud (bedrog) has been regulated in Article 1328 of the Civil Code, but the substantial understanding has not been regulated in Article 1328 of the Indonesian Civil Code, fraud in Dutch civil law is regulated in article 3:44 Nieuw Burgerlijk Wetboek. The recommendation that the author can note is that as one of the countries adopted by Indonesia, it is appropriate for Fraud to get elaboration and technical procedures to identify Fraud as a defect of will. Bedrog is defined by definition as an act in which a party entices another party to take certain legal actions by, among others: making false and deliberate statements; deliberately not disclosing the fact that it should be mandatory to disclose, and intentionally withholding or providing incomplete information. The formulation of the definition in the NBW should be a reference in the renewal of the Civil Code related to Bedrog.